2020
DOI: 10.1109/access.2020.2982223
|View full text |Cite
|
Sign up to set email alerts
|

Research on Remaining Useful Life Prognostics Based on Fuzzy Evaluation-Gaussian Process Regression Method

Abstract: To achieve efficient and accurate remaining life prediction and effectively express the uncertainty of prediction results, this paper proposes a remaining life prediction method based on fuzzy evaluation-Gaussian process regression (FE-GPR). First, the prediction of the remaining useful life (RUL) is affected by unknown variables, such as the environment, and it is difficult to achieve accurate predictions. It is necessary to effectively express the uncertainty of such prediction results. In this paper, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…A BPNN [28] is a multilayer feedforward neural network in an artificial neural network, which is the most representative and extensive approach. The GPR [29], [34]- [36] is designed based on the Bayesian framework [37], [38] and is widely used in prediction tasks [39]- [41]. In SOH estimation, the inputs for the BPNNbased method, the GPR-based method, and the standard SVM-based method are also HF3 and HF4.…”
Section: Soh Estimation Results and Discussionmentioning
confidence: 99%
“…A BPNN [28] is a multilayer feedforward neural network in an artificial neural network, which is the most representative and extensive approach. The GPR [29], [34]- [36] is designed based on the Bayesian framework [37], [38] and is widely used in prediction tasks [39]- [41]. In SOH estimation, the inputs for the BPNNbased method, the GPR-based method, and the standard SVM-based method are also HF3 and HF4.…”
Section: Soh Estimation Results and Discussionmentioning
confidence: 99%
“…For the long-term RUL prediction of the battery, the RMSE and MAE are no more than 10 cycles and 6 cycles, respectively. Kang et al (2020) proposed an RUL prediction method based on Fuzzy Evaluation Gaussian Process Regression (FE-GPR). Combined with the characteristics of the GPR method, the observation data is preprocessed through fuzzy evaluation.…”
Section: Gaussian Process Regressionmentioning
confidence: 99%
“…Researchers usually combine fuzzy logic with other techniques for getting better prognosis performance. Kang et al [148] applied fuzzy evaluation-Gaussian process regression model to estimate the RUL in the case of limited data. Cheng et al [149] developed a novel RUL prediction method using adaptive neuro-fuzzy inference system (AFNIS) and particle filtering to automatically detect gearboxes faults in wind turbines.…”
Section: Fuzzy Systemsmentioning
confidence: 99%
“…12 The RUL prediction results with different prediction starting point and prediction methods [169] the short-term state of health of lithium-ion batteries and applied GPR model to assess the RUL by the mapping relationship between state of health and RUL. Kang et al [148] used Gaussian process regression based on fuzzy evaluation to achieve RUL estimation of the lithium battery. They found that the proposed approach can avoid over-fitting in the case of finite data.…”
Section: Gaussian Process Regressionmentioning
confidence: 99%